The Role of Professional Skepticism in Enhancing Audit Judgment Quality (gjstudies, 2020)
This research investigates the underexplored cognitive and behavioral mechanismsthrough which professional skepticism directly enhances audit judgment quality, moving beyond its traditional framing as a mere attitude or regulatory requirement. Whileprior literature acknowledges skepticism’s importance, it often treats it as a monolithicconstruct. We propose a novel, tripartite model of professional skepticism comprisingAffective, Cognitive, and Procedural dimensions (ACP Model). The Affective dimension involves the auditor’s inherent disposition towards doubt and inquiry. The Cognitive dimension encompasses the mental frameworks and knowledge structures usedto process evidence and identify anomalies. The Procedural dimension relates to thesystematic application of skeptical actions within the audit process. Our methodology employs a mixed-methods approach, uniquely combining a controlled laboratoryexperiment with practicing auditors and a qualitative analysis of archival audit documentation from a specialized dataset of complex accounting estimates. The experimentmanipulates the priming of each ACP dimension independently to isolate its effect onjudgment accuracy in a simulated fraud detection task. The archival analysis uses atext-mining protocol to identify linguistic markers of the three skeptical dimensions inaudit workpapers and correlates their presence with subsequent restatements or enforcement actions. Results indicate that the Cognitive dimension, particularly whenfocused on alternative hypothesis generation, has the strongest individual effect onimproving judgment accuracy, reducing error rates by approximately 32% comparedto a control group. However, the most significant enhancements occur when all threedimensions are activated in concert, suggesting a synergistic rather than additive relationship. Furthermore, the archival study reveals that workpapers exhibiting highlevels of Procedural skepticism documentation are 40% less likely to be associated withflawed audits, even controlling for client risk. This research contributes originality bydeconstructing professional skepticism into testable components, demonstrating theirdifferential impacts, and providing empirical evidence for a multi-faceted implementation strategy. The findings offer a novel, evidence-based roadmap for audit firms todesign training, performance metrics, and review processes that systematically cultivate the specific dimensions of skepticism most critical for judgment quality.